High-flow nasal cannula oxygen therapy versus non-invasive ventilation in healthy respiratory physicians: a non-randomized study - Ye, Hong; Xiang, Dandan; Zhu, Xiangyu; Du, Xiuwei; Shang, Shengyun; Xu, Jing; Li, Yu; Cheng, Yunyun; Yang, Zhongfei (Frontiers in Medicine, 2025)
BackgroundHigh-flow nasal cannula (HFNC) and non-invasive ventilation (NIV) are commonly used for respiratory support. This study aims to first establish whether to use HFNC or NIV based on comfort levels, and subsequently evaluate diaphragmatic function under equivalent comfort levels to determine the optimal modality for clinical application.MethodsA self-controlled, non-randomized study was conducted with 10 healthy respiratory physicians as participants. Each subject was exposed to different HFNC settings, including flow rates of 20, 40, and 60 L/min at both 33 and 37°C. Additionally, participants were assessed under NIV mode. Comfort levels as the primary outcome were evaluated using the Visual Numerical Scale (VNS). Meanwhile, vital signs and diaphragmatic mobility were monitored through an electrocardiograph and ultrasound.ResultsHFNC at a flow rate of 20 L/min provided greater comfort than NIV. However, as the flow rate increased, this comfort benefit decreased. At 40 L/min, comfort levels were similar between HFNC and NIV, while at 60 L/min, HFNC was less comfortable than NIV. Notably, temperature variations between 33 and 37°C had no significant effect on comfort. In addition, under conditions of similar comfort, HFNC demonstrated slightly greater diaphragmatic mobility compared to NIV.ConclusionOur study indicated HFNC was the preferred choice for providing respiratory support at low to moderate flow rates in healthy volunteers not requiring respiratory support. By contrast, at higher flow rates, NIV discomfort was lower than HFNC discomfort.